Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 10167777 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "Country is Brazil", "Country is Colombia", "Country is Peru", "Country is Ecuador", "Country is Suriname" ] }, "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 10167777 records from 1372 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004790-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences